2015
DOI: 10.15639/teflinjournal.v21i2/172-185
|View full text |Cite
|
Sign up to set email alerts
|

Language and Gender in English Language Teaching

Abstract: his paper highlights the impact ofgender differences in English Language Teaching. It explores students’ learning styles as affected by the notions about men and women differences in communication. The data collected in 2008 from 20 males and 20 females’ English students of the State University of Makassar. It is to reveal their attitudes towards speaking to different sex, strategy to express opinion, group work preferences, activeness/passiveness, and their perception to increase English skills dealing with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…This appears as ICT provides useful software or programs for the teachers to check their students' assignments which can save their time and energy rather than check them manually one by one. This finding is supported by previous studies which revealed the use of ICT can facilitate teachers to assess and monitor their students' progress easier than before [14] [15].…”
Section: Teachers' Perceived the Effectiveness Of Ict During Covid-19supporting
confidence: 85%
“…This appears as ICT provides useful software or programs for the teachers to check their students' assignments which can save their time and energy rather than check them manually one by one. This finding is supported by previous studies which revealed the use of ICT can facilitate teachers to assess and monitor their students' progress easier than before [14] [15].…”
Section: Teachers' Perceived the Effectiveness Of Ict During Covid-19supporting
confidence: 85%
“…On the other hand, men in similar circumstances do not show this tendency. This seems in line with (Mahmud, 2015) notion that women tend to speak with reference to the rules of politeness, conversational implicates and interpersonal exploration, while men tend to speak with reference to the rules of conversation and straight factual communication.…”
Section: Gender Differences In Communicationsupporting
confidence: 86%
“…A classroom interaction is essentially a social interaction through language with teacher and students as its participants. Such an interaction is built by two components; teacher talk and student talk (Mahmud, 2015). Being the one in charge, teacher controls the teaching and learning process in the classroom, therefore, whatever he or she says determines how the process goes and students' involvements in the classroom activities.…”
Section: Instructional Talkmentioning
confidence: 99%
“…The communication system delivers a code in the forms of sounds, sentences, and words that are affected by several factors, such as gender, culture, class, and race (Aitchison & Wardaugh, 1987). Cultural conditions and social stereotypes control gender roles in communication, as reflected in how men and women use language (Heilman, 2012;Mahmud, 2015;Phillips, 2005). Lakoff (1973) already highlights the difference in language use between men and women and how they are controlled by society and certain cultural values, resulting in language variations that either marginalize women or are internalized by women and further the marginalization (Coates, 2013;Sunderland, 2006).…”
Section: Introductionmentioning
confidence: 99%